2019
DOI: 10.1111/jspn.12271
|View full text |Cite
|
Sign up to set email alerts
|

The symptom experience of adolescents with concussion

Abstract: Purpose The incidence of concussions in adolescents has increased in recent years. Concussion causes an array of symptoms that can interfere with the daily life of an adolescent, yet the symptoms and recovery vary greatly. Concussion management is based on expert consensus guidelines but they are not specific for adolescents and it is unclear how adolescents actually manage their symptoms. This study aimed to describe the symptom experience of adolescents with a concussion and their self‐management strategies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Previous qualitative research with adolescents has shown that four categories-school, mood, and physical and social activities-emerged when asking how SRC symptoms affected aspects of life. 43 In addition, the ability to control environmental symptom-exacerbating factors, such as noise levels and bright lights, led to different strategies to self-manage symptoms. 43 Among the athletes in this study, there were small differences between Black and White ath- letes in video game use, but a greater proportion of White athletes reported that they slept more (34.6% vs 27.8%) and watched less television (63.5% vs 52.8%) than the proportion of Black athletes.…”
Section: Changes In Daily Activity and Sport Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Previous qualitative research with adolescents has shown that four categories-school, mood, and physical and social activities-emerged when asking how SRC symptoms affected aspects of life. 43 In addition, the ability to control environmental symptom-exacerbating factors, such as noise levels and bright lights, led to different strategies to self-manage symptoms. 43 Among the athletes in this study, there were small differences between Black and White ath- letes in video game use, but a greater proportion of White athletes reported that they slept more (34.6% vs 27.8%) and watched less television (63.5% vs 52.8%) than the proportion of Black athletes.…”
Section: Changes In Daily Activity and Sport Behaviormentioning
confidence: 99%
“…43 In addition, the ability to control environmental symptom-exacerbating factors, such as noise levels and bright lights, led to different strategies to self-manage symptoms. 43 Among the athletes in this study, there were small differences between Black and White ath- letes in video game use, but a greater proportion of White athletes reported that they slept more (34.6% vs 27.8%) and watched less television (63.5% vs 52.8%) than the proportion of Black athletes. The median duration of sleep disturbance following SRC has been shown to be approximately 16 days, 44 and the sleep changes reported among the White athletes could be tied to their longer symptom duration.…”
Section: Changes In Daily Activity and Sport Behaviormentioning
confidence: 99%
“…In Ontario, the annual incidence of concussion is 1% of the population, with children having the highest incidence (3,600 per 100,000 individuals) (1,2). A concussion has detrimental impacts on a child's physical, psychological, and academic performance (3)(4)(5), affecting school attendance (6), participation in sports or social activities (7), and quality of life (8)(9)(10). Although many children become symptom-free within 2 weeks, approximately one-third of children experience prolonged symptoms past 1 month, referred to as persistent post-concussion symptoms (PCS) (11,12).…”
Section: Introductionmentioning
confidence: 99%